2022
DOI: 10.3389/fonc.2022.962920
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from gastric epithelial GES-1 cells infected with Helicobacter pylori promote changes in recipient cells associated with malignancy

Abstract: Chronic Helicobacter pylori (H. pylori) infection is considered the main risk factor for the development of gastric cancer. Pathophysiological changes in the gastric mucosa initiated by this bacterium can persist even after pharmacological eradication and are likely attributable also to changes induced in non-infected cells as a consequence of intercellular communication via extracellular vesicles (EVs). To better understand what such changes might entail, we isolated EVs from immortalized normal gastric GES-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…This transfer leads to the induction of IL-8 production and subsequent morphological cellular changes [ 64 ], potentially contributing to the induction of malignancy. As a result, it has been reported that the resident cells and their EVs serve as mediators in relation to the induced pathology [ 65 ].…”
Section: Evs As Mediators In Gastroenteric Pathogenesis and Biomarker...mentioning
confidence: 99%
“…This transfer leads to the induction of IL-8 production and subsequent morphological cellular changes [ 64 ], potentially contributing to the induction of malignancy. As a result, it has been reported that the resident cells and their EVs serve as mediators in relation to the induced pathology [ 65 ].…”
Section: Evs As Mediators In Gastroenteric Pathogenesis and Biomarker...mentioning
confidence: 99%
“…GES-1 gastric cells, an immortalized cell line from the normal gastric epithelium (RRID: CVCL_EQ22, Universidad Católica de Chile), were maintained as monolayer cultures in RPMI1640 medium supplemented with 10% FBS and 1% antibiotics (10,000 U/mL penicillin and 10,000 µg/mL streptomycin), in an atmosphere containing 5% CO 2 at 37 • C [36].…”
Section: Cell Culturementioning
confidence: 99%
“…2 ). To investigate the changes in EVs released from gastric host cells during H. pylori infection, González et al [ 62 ] isolated and characterized EVs from H. pylori -infected and non-infected human gastric epithelial cells GES-1 (designated as EVHp + and EVHp-, respectively). They demonstrated that extracellular vesicles from H. pylori -infected gastric epithelial cells promoted alterations in receptor cells associated with malignancy.…”
Section: Introductionmentioning
confidence: 99%